SISTEM INFORMASI KEAHLIAN DOSEN BERBASIS WEB JURUSAN SISTEM INFORMASI UIN SUSKA RIAU - M. VHEROLLY IRAQA; Ananda (Politeknik Negeri Bengkalis, 2023)
Expertise lecturers are an ability possessed by each lecturer (individual) to perform the functions and duties of lecturers that teach, serve and researching, in the development of science, especially lecturer of Information Systems Faculty of Science and Technology UIN Suska Riau difficult to find or obtain resources that will help to support scientific knowledge. Lecturer in the Department of Information Systems Faculty of Science and Technology UIN Suska Riau in finding sources of information before a meeting a meeting aiming to get science information is sought from both the work experience of lecturers, the expertise of faculty and research faculty with the sharing of information between lecturers to one another in this way makes the lecturer many find difficulty in getting information quickly, have a meeting because the meeting in advance, some professors do not know each other so that information seekers lecturer shy to ask questions, and in doing only partially meeting the lecturers are present so that the information to be searched limited. Therefore, of course, lecturers need a media liaison between lecturers with other professors who are able to provide information quickly, easily, the latest, and wide or more, so teachers can interact directly (online). Thus it was established a media information that provides information on faculty expertise, work experience lecturer and research faculty. Making the system will be done in the form of computerized development by utilizing online media, there was made a professor of information systems web-based membership.